2013
DOI: 10.1021/jp3102628
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Recrystallization of Water in Concentrated Aqueous Solution of Poly(ethylene glycol)

Abstract: Crystallization behavior of water in a concentrated aqueous solution of poly(ethylene glycol) (PEG) with a water content of 37.5 wt % was investigated by temperature variable mid-infrared (mid-IR) spectroscopy in a temperature range of 298-170 K. The mid-IR spectrum of water at 298 K showed that a large water cluster was not formed and that most of the water molecules were associated with the PEG chain. Ice formation, however, occurred as found in previous studies by differential scanning calorimetory. Ice for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…They suggest that PEG chain can adopt various conformations around C–C and C–O bonds of O–C–C–O unit segment. The trans–gauche–trans ( tgt ) conformation in the O–C–C–O segment adopted by solid PEG has been reported to be present even in PEG–water mixtures. ,, The tgt conformation is a basic unit of 7 / 2 (seven chemical units and two turns) helical segment formed in PEG chains as confirmed by X-ray diffraction study . For the helical conformation of PEG, the closest oxygen–oxygen distance is similar to that between neighboring water molecules in water .…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…They suggest that PEG chain can adopt various conformations around C–C and C–O bonds of O–C–C–O unit segment. The trans–gauche–trans ( tgt ) conformation in the O–C–C–O segment adopted by solid PEG has been reported to be present even in PEG–water mixtures. ,, The tgt conformation is a basic unit of 7 / 2 (seven chemical units and two turns) helical segment formed in PEG chains as confirmed by X-ray diffraction study . For the helical conformation of PEG, the closest oxygen–oxygen distance is similar to that between neighboring water molecules in water .…”
Section: Introductionmentioning
confidence: 88%
“…10 In water-poor solutions (70−80 wt %) however, PEG favors a compact helical structure, which is similar to that of crystalline PEG, with some random-coil segments. 21,22 Conformational Transition of PEG. To support these findings on the interplay of PEGDME conformational transition with water structure and dynamics upon increasing crowder concentration, we further compared the C−H stretching vibrations of PEGDME at ∼2919 cm −1 (associated with random-coil configuration of PEGDME) and ∼2883 cm −1 (both random-coil and tgt conformations of PEGDME) (Figure 4).…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study using a PEG aqueous solution with a W C of 37.5 wt% revealed that the recrystallizable water in this solution had two different types of hydration structures and that their recrystallization temperatures were different. 54 The perfect vitrification of the PEGwater system was probably related to the existence of these two different types of hydration structure. In the present study, to reveal the cause of the perfect vitrification, the thermal properties of PEG aqueous solutions with various W C values in the range 3651 wt% were investigated by temperature-variable Fourier-transform mid-infrared spectroscopy (TVFT-IR).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, macromolecular crowding does not affect interstitial water dynamics but moderately slows the dynamics of tightly associated ether water. PEGDME responds to this high crowding by adopting a crystalline structure similar to solid PEG, in which its contact with water is minimized but optimized. This enhanced intermolecular interaction favors the helical conformation of PEGDME and water pooling. Hence, the water dynamics remain unperturbed and the water associated with ether oxygen shows a marginal dependence on crowding due to conformational flexibility.…”
mentioning
confidence: 99%